2021
DOI: 10.3390/metabo11060370
|View full text |Cite
|
Sign up to set email alerts
|

Stable Isotope Abundance and Fractionation in Human Diseases

Abstract: The natural abundance of heavy stable isotopes (13C, 15N, 18O, etc.) is now of considerable importance in many research fields, including human physiology. In fact, it varies between tissues and metabolites due to isotope effects in biological processes, that is, isotope discriminations between heavy and light isotopic forms during enzyme or transporter activity. The metabolic deregulation associated with many diseases leads to alterations in metabolic fluxes, resulting in changes in isotope abundance that can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 67 publications
0
16
0
Order By: Relevance
“…The mass spectrometry technique is used to detect metabolic tracking from stable isotope tracers [ 23 ]. 13C is the predominant isotope used because of its universal distribution in almost every cellular organic molecule [ 24 ].…”
Section: Amino Acid As Energy Source and Tissue Builder In Bonesmentioning
confidence: 99%
“…The mass spectrometry technique is used to detect metabolic tracking from stable isotope tracers [ 23 ]. 13C is the predominant isotope used because of its universal distribution in almost every cellular organic molecule [ 24 ].…”
Section: Amino Acid As Energy Source and Tissue Builder In Bonesmentioning
confidence: 99%
“…The natural abundance of heavy stable isotopes such as 13 C, 15 N and 18 O varies between tissues and metabolites due to isotope fractionation effects in biological processes. Indeed, as recently pointed out by Hastuti et al [ 295 ], variations in stable isotope ratios of essential elements can reflect alterations in their homeostasis resulting from physiological changes in malignancies with higher sensitivity than concentrations do.…”
Section: Geochemical Variables and Diseasementioning
confidence: 95%
“…The unclear impact of biological stress on bone isotopic values is one of the most important factors limiting the testimonial power of isotopic reconstruction of past diets (e.g., Reitsema, 2013). Although in recent years the corpus of bone isotopic data from medical or paleopathological cases has increased notably (for review, see Drtikolová Kaupová et al, 2021), most of the information on the mechanisms driving isotopic shifts during periods of nutritional or biological stress is still based on the examination of tissues with much more rapid turnover, most commonly hair but also nails, plasma, saliva, or urine (Reitsema, 2013; Tea et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…On the basis of controlled feeding experiments as well as direct observation in humans with, for example, eating disorders or pregnancy complications, it has repeatedly been demonstrated that pathophysiological processes may affect stable isotope fractionation and distribution in the body (for review, see, e.g., Reitsema, 2013; Tea et al, 2021). Most commonly, health conditions linked to wasting have the potential to influence the isotopic values of proteins synthetized over the course of the disease.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation